The Role of The Sekala Brak Kingdom Leadership In Building Local Politics and Harmonizing Religions in Lampung Province - Ruslan, Idrus; Zarkasi, Ahmad; Yudha, Gesit (Universitas Islam Negeri Raden Intan Lampung, 2023)
Traditional leaders play an important role in assisting the country's government system, building local politics and harmonization of religious communities, which is evident through the concept and objectives of the customary leadership of the Sekala Bekhak Kingdom. The system aims to influence the community to continue cultivating customs for the good and common goals. The magnitude of the role of traditional leaders of the Sekala Bekhak Kingdom prompted this study. This study uses a qualitative method with a phenomenological approach, the data sources used are secondary and primary data. The research subjects were the Prime Minister of the Kingdom of Sekala Brak, and Sultan Kaksian Belungu. The findings of this study are that traditional leaders can control customary activities, benefit the community and form a community that is always participatory in community activities. In building the harmony of religious communities, Suttan Saibatin always instills the Piil Pesenggiri principle which includes human values, being mutually open to the environment and always accepting immigrants, carrying out the values of Sakai Sambayan, Nemui Nyimah, Nengah Nyapur, and Bejuluk Beadek and implementing the Muakhi culture which being a form of brotherhood in order to realize a sense of security even though they are of different ethnicities so that they can get a position in the frame of kemuakhian.